REPRESENTING THE FEMALE BODY AND THE CON-CEPT OF FEMININE BEAUTY IN THE CONTEXT OF AS-SAMESE PROVERBS - Baruah, Mandakini (Proverbium - Yearbook, 2015)
Female body has always been considered to be the symbol of grace, modesty, simplicity and submissiveness. This stereotype is strengthened in oral literature. Proverbs constitute one of the most important components of oral literature. Beauty is universally considered the main criterion of women. However, every society has its own notion of beauty regarding women. There are certain stereotypical expectations of female body in every society. But the standards of beauty differ from people to people, society to society. If a woman does not fulfill these norms of the society that she belongs to, she is not regarded as a perfect woman. Women, who are outside the prevailing norms of beauty, are considered to be abnormal, witch, evil-like, disobedient, cruel etc. Therefore, notions regarding female body are socially con-structed. Such, and many other related norms of feminine beauty and the female body are found in women related Assamese proverbs. The present paper tries to analyze the construction of ideas regarding womanhood with special reference to female body and feminine beauty through Assamese proverbs. It is an ethnographic study of the Nagaon district of middle Assam in India.